2022
DOI: 10.1186/s12889-022-12764-2
|View full text |Cite
|
Sign up to set email alerts
|

A trend analysis of the prevalence of opioid misuse, social support, and suicide attempt among American Indian/Alaska native high school students in New Mexico: 2009–2019 Youth Risk Resiliency Survey (YRRS)

Abstract: Background American Indian and Alaska Native (AI/AN) youth face stark inequities in opioid misuse, social support, and suicide attempt. This study examined trends in these behavioral measures among AI/AN students in New Mexico (NM). Methods Using the NM oversampled Youth Resiliency and Risk Survey (NM-YRRS, 2009 – 2019: odd years), prevalence estimates of opioid misuse, social support (SS), and suicide attempt for AI/AN high school students were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Second, Hameed et al (2018) found an adverse link between social support and EBPs among adolescents [53]. Agyemang et al (2022) found youth with low social support had the highest prevalence of suicide attempt [54]. Conversely, high social support contributed to increasing resilience and thus protecting adolescents from EBPs in Chinese adolescents [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Second, Hameed et al (2018) found an adverse link between social support and EBPs among adolescents [53]. Agyemang et al (2022) found youth with low social support had the highest prevalence of suicide attempt [54]. Conversely, high social support contributed to increasing resilience and thus protecting adolescents from EBPs in Chinese adolescents [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…These models highlight key issues such as emotional dysregulation, interpersonal conflicts, trauma exposure, and the protective roles of social support and cultural connectedness. Additional empirical literature supports the emphasis of these models on social support and cultural connectedness as protective factors against suicide among Native youth 12–17 . Other important factors to investigate among American Indian, Alaska Native, and Native Hawaiian (AI/AN/NH) college students include gender and sexual minority status, mental illnesses/disorders, eating disorders, sleeping disorders, and other substance use disorders, which are associated with suicide risk in other studies 18–25 .…”
Section: Introductionmentioning
confidence: 95%
“…Additional empirical literature supports the emphasis of these models on social support and cultural connectedness as protective factors against suicide among Native youth. 12 , 13 , 14 , 15 , 16 , 17 Other important factors to investigate among American Indian, Alaska Native, and Native Hawaiian (AI/AN/NH) college students include gender and sexual minority status, mental illnesses/disorders, eating disorders, sleeping disorders, and other substance use disorders, which are associated with suicide risk in other studies. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Among AI/AN/NH college students, 22.1% report suicidal ideation, 11.8% attempt suicide, and 19.6% report self‐injury.…”
Section: Introductionmentioning
confidence: 99%
“…Acculturative stress is a particularly potent risk factor for opioid use among youth, and first, second and '1.5' generation immigrant youth in particular [114][115][116][117][118][119], given the higher levels of social/emotional malleability and lower levels of resilience that characterise this age group. To this end, racial/ethnic minorities tend to have lower rates of help-seeking and treatment for mental illness in comparison to Whites [120,121], in part due to intracultural stigma and insurance/geographic barriers, which can motivate nonmedical use of opioids as a coping mechanism.…”
Section: The Pronounced Role Of Acculturative Stress Mental Illness A...mentioning
confidence: 99%